Doubling of Electrochemical Parameters via the Pre-intercalation of Na+ in Layered MnO2 Nanoflakes Compared to a-MnO2 Nanorods - Rajan, Jose; Izan Izwan, Misnon; Jamil, Ismail; K. F., Chong; Vidyadharan, Baiju (Royal Society of Chemistry, 2015)
The pre-intercalation of Na+ ions in layered birnessite-MnO2 is shown to have a dramatic influence on its electrochemical properties. Electrochemical studies showed the doubling of the specific capacitance and energy density in the layered Na–MnO2 nanoflakes compared to the MnO2 nanorods.